Hoidettujen talvilaitumien vaikutus hirvituhoihin mäntytaimikoissa. - Lääperi, Ari (The Society of Forestry in Finland - The Finnish Forest Research Institute, 2009)
Moose (Alces alces) cause considerable damage to traffic, agriculture and forestry in Finland. This has resulted in pressure to reduce the moose stock. The proposal that moose damage might be reduced by providing alternative sites was investigated. In spring 1987, six feeding sites and six 1-ha control areas were selected in Scots pine (Pinus sylvestris) plantations in the Ruokolahti-Imatra area, Finland. Mineral licks and aspen (Populus tremula) and Scots pine tops were provided on the feeding sites. These sites were also treated with nitrogen fertilizer. Before 1987, moose had destroyed four plantations in the immediate surroundings of the experimental areas. During the period 1987-89 only one plantation was destroyed. This was attributed to the setting up of the feeding sites. It was also noted that the reduction in damage was partly due to a probable decrease in the moose population. The number of damaged plants near one of the feeding sites was significantly greater than the damage near its corresponding control area, because there was not enough food for the moose population at this feeding site. It is concluded that the establishment of winter feeding sites may be a practical method for reducing moose damage and keeping the moose stock at its present size. The main problem was the increased risk of damage near feeding sites if the food is not replaced quickly enough.